2017
DOI: 10.1111/sjop.12345
|View full text |Cite
|
Sign up to set email alerts
|

To wait or not to wait? Improving results when interviewing intoxicated witnesses to violence

Abstract: Witnesses to violent crimes are often alcohol intoxicated, but few studies have investigated the impact of alcohol on witness reports. This study investigated how alcohol intoxication and time of interview affected reports of intimate partner violence (IPV). One hundred thirty six healthy men (N = 66) and women (N = 70) were randomized to an alcohol group (0.8g/kg for men, 0.75g/kg for women) (N = 70) or control group (N = 66), given juice. Participants consumed drinks in a laboratory setting before they witne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 50 publications
5
45
1
Order By: Relevance
“…In Hildebrand Karlén et al . (), this reduction in completeness of the report was found among witnesses with BAC > 0.08 both in the immediate interview condition and in the one‐week delay interview condition. This reduction primarily consisted of less reporting of actions (i.e., presumably high salience details) between the involved parties in the scenario, while reporting of objects (i.e., low salience details) was not affected.…”
Section: Interviewing Intoxicated Witnesses: Summary Of Empirical Stumentioning
confidence: 71%
See 4 more Smart Citations
“…In Hildebrand Karlén et al . (), this reduction in completeness of the report was found among witnesses with BAC > 0.08 both in the immediate interview condition and in the one‐week delay interview condition. This reduction primarily consisted of less reporting of actions (i.e., presumably high salience details) between the involved parties in the scenario, while reporting of objects (i.e., low salience details) was not affected.…”
Section: Interviewing Intoxicated Witnesses: Summary Of Empirical Stumentioning
confidence: 71%
“…The same pattern has been found for sober participants in a study using a witness context (Pansky & Nemets, ). Studies of intoxicated witnesses’ immediate and delayed free recall have also found a decreased quantity but maintained accuracy of the reported information and used quantity‐accuracy trade‐off as a theoretical framework for these findings (Hildebrand Karlén et al ., ; see also Flowe et al ., for a discussion).…”
Section: Theories Proposed Relevant For When and Why Alcohol Impairs mentioning
confidence: 88%
See 3 more Smart Citations